Biological risks in professionals working in the mobile urgency service - Carvalho, Tatiana de Sousa Sobral; Costa, Adriana Ferreira; Martins, Wanessa Castro; Gonçalves, Maria Claudia; Monteiro, Sílvio Gomes (Ciência e Natura, 2018)
This descriptive, cross-sectional study aims to evaluate the biological risks among professionals who work in the Mobile Emergency Service of the Metropolitan Region of São Luís - MA. The data were collected from 177 professionals from basic and advanced support units between February and April 2018, using a structured questionnaire. While a high prevalence of exposure to biological risks was observed among all the subjects, men were found to be at a higher risk. The main source of contamination was blood, mainly affecting the whole skin during the procedure of immobilization. It was evidenced that most of the subjects did not complete the accident report and did not adhere to any post-exposure protocols. It is believed that the development of educational, safety and health measures can minimize the occupational hazards and accidents among the SAMU professionals, who are providers of indispensable service to society, even if susceptible to various environmental risks.